A kind of impact-resistant ultra-high performance concrete and its preparation method and application
Through the combination of modified steel fibers and multi-scale magnesium oxide, the problem of ultra-high performance concrete is solved, and the problem of explosive and self-shrinkage rate is large under impact loads is significantly improved, and its impact resistance is achieved, and efficient resource recovery and re-recycling are achieved. Utilization reduces costs and environmental pollution.
Patent Information
- Application Number
- CN202411375187.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-30
AI Technical Summary
Ultra-high performance concrete is prone to burst under impact loads, and its large self-shrinkage rate leads to poor bonding performance between steel fibers and the matrix, limiting its widespread application in the field of impact resistance.
Modified steel fibers and multi-scale magnesium oxide are used to modify the steel fibers through silane coupling agent hydrolysate, and micro- and nano-scale magnesium oxide are added to the concrete, combining waste tire steel fibers to improve the adhesion between the steel fibers and the matrix. Junction performance and impact resistance.
It significantly improves the impact resistance of ultra-high performance concrete, reduces costs, achieves firm bonding between steel fibers and the matrix, reduces environmental pollution, and reflects the concept of green and sustainable development.
Smart Images

Figure CN118894705B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and specifically relates to an impact-resistant ultra-high performance concrete and a preparation method and application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Ultra-high performance concrete (UHPC) has attracted widespread attention for its excellent mechanical properties and durability, and can be widely used in the field of construction (including bridges, high-rise buildings and other infrastructure). At present, the scope and quantity of UHPC applications are far lower than expected. The main reasons are: 1. When UHPC is used in important infrastructure such as bridges, these infrastructures are often subjected to dynamic loads such as impact and explosion; due to the ultra-high strength of the UHPC matrix, it is also brittle at the same time, which makes it very easy to burst under impact loads. 2. The self-shrinkage rate of UHPC is large, which makes the bonding performance between the matrix and the steel fiber worse. When the interface between the steel fiber and the matrix is damaged, the steel fiber reinforcement effect will fail, and eventually the cement-based material will crack. Both aspects have seriously affected the application of UHPC in the field of impact resistance. Therefore, how to effectively deal with the interfacial bonding performance between the steel fiber and the UHPC matrix and the problem of bursting easily under dynamic impact loads has become one of the important challenges restricting its widespread application. Summary of the invention
[0004] In order to address the deficiencies of the prior art, the purpose of the present invention is to provide an impact-resistant ultra-high performance concrete and a preparation method and application thereof. The modified steel fiber is added to UHPC, and two different sizes of magnesium oxide are added, which can reduce the cost of UHPC while improving its impact resistance.
[0005] In order to achieve the above object, the technical solution of the present invention is:
[0006] In a first aspect, the present invention provides an impact-resistant ultra-high performance concrete, which is prepared from the following raw materials in parts by weight:
[0007] 15-30 parts of micron-grade magnesium oxide, 15-30 parts of nano-grade magnesium oxide, 800-900 parts of cement, 100-130 parts of silica fume, 90-120 parts of fly ash microspheres, 280-320 parts of medium sand, 650-750 parts of fine sand, 130-170 parts of modified steel fiber, 15-30 parts of water reducer and 140-160 parts of water;
[0008] The modified steel fiber is a steel fiber modified by a silane coupling agent hydrolyzate; the length of the steel fiber is 1.3-50 mm, and the diameter is 0.10-0.20 mm;
[0009] Among the steel fibers, the volume percentage of steel fibers with a length of 1.3-20 mm is 25-35%, the volume percentage of steel fibers with a length of 20-40 mm is 35-45%, and the volume percentage of steel fibers with a length of 40-50 mm is 25-35%.
[0010] Optionally, the steel fiber is a straight steel fiber or a waste tire steel fiber.
[0011] The waste tire steel fiber is obtained by stripping and cutting the steel wire belt layer in the waste tire through physical means and other simple processes; the bending shape, end hooks and rough surface of the waste tire steel fiber formed by mechanical processing during the recycling process can be utilized to make it more firmly bonded to the substrate.
[0012] In a second aspect, the method for preparing the above-mentioned impact-resistant ultra-high performance concrete comprises the following steps:
[0013] S1. Soak the steel fiber in a sodium hydroxide solution with a mass concentration of 20-35% for 20-40 min;
[0014] S2, soaking the washed steel fiber in a silane coupling agent hydrolyzate for 7-15 minutes, then taking it out, and drying it at 100-120° C. for 1.5-2.5 hours to obtain a modified steel fiber;
[0015] S3, mixing micron-sized magnesium oxide, nano-sized magnesium oxide, cement, silica fume, fly ash microbeads, medium sand and fine sand, and dry-mixing for 3-5 minutes to obtain a first mixed material;
[0016] S4, adding water and a water reducing agent to the first mixed material, stirring for 5 to 7 minutes, to obtain a second mixed material;
[0017] S5, adding modified steel fiber to the second mixed material in a stirring state for several times, stirring for 6 to 8 minutes, to obtain a concrete mixture;
[0018] S6. Cast the concrete mixture into a mold, cover it with a curing film, demould it after a set time and cure it to the specified age.
[0019] In a third aspect, the present invention provides the use of the above-mentioned impact-resistant ultra-high performance concrete in the construction of buildings.
[0020] The beneficial effects of the present invention are:
[0021] 1. The length range of the steel fibers added in the present invention is large, among which the longer steel fibers can better inhibit the expansion of larger cracks, and the shorter steel fibers can inhibit the expansion of microcracks; at the same time, the present invention improves the bonding performance between the steel fibers and the UHPC matrix through silane modification, and reduces the self-shrinkage of UHPC through multi-scale magnesium oxide compensation shrinkage, so as to further improve the bonding performance between the steel fibers and the UHPC matrix, and obtain UHPC with excellent impact resistance.
[0022] 2. The present invention effectively utilizes waste rubber tires, and obtains a new type of steel fiber material - waste tire steel fiber after a simple process such as peeling and cutting the steel wire belt layer by physical means, and applies it to UHPC. The recycling process of waste tire steel fiber causes most of it to be curved, and there are end hooks at its ends, which can strengthen the anchoring effect between the steel fiber and the matrix; and the surface is rougher, so that the steel fiber and the matrix are more firmly bonded. Therefore, replacing the straight copper-plated steel fiber with waste tire steel fiber can reduce the cost of UHPC while further improving the mechanical properties of UHPC. This resource utilization not only reduces the environmental pollution of industrial waste, but also embodies the concept of green and sustainable development. Through the present invention, the efficient recycling and reuse of industrial waste is achieved, which promotes the environmental friendliness and resource conservation of the building materials industry, and has important environmental value and social benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0024] Figure 1 These are the actual pictures of the waste tire steel fiber and the copper-plated straight steel fiber in Example 1; among them, (a) is the actual picture of the copper-plated straight steel fiber; (b) is the actual picture of the waste tire steel fiber.
[0025] Figure 2 The dynamic stress-strain curves of the ultra-high performance concrete of Example 1 at different strain rates.
[0026] Figure 3 The dynamic stress-strain curves of ultra-high performance concrete of comparative example 1 at different strain rates.
[0027] Figure 4 The dynamic stress-strain curves of ultra-high performance concrete of comparative example 2 at different strain rates.
[0028] Figure 5 The dynamic stress-strain curve of ultra-high performance concrete of comparative example 3 at different strain rates.
[0029] Figure 6 These are the impact compression failure morphology diagrams of the ultra-high performance concrete of Example 1 at different strain rates; (a) is the impact compression failure morphology diagram when the air pressure value is 0.4 MPa, (b) is the impact compression failure morphology diagram when the air pressure value is 0.5 MPa, (c) is the impact compression failure morphology diagram when the air pressure value is 0.6 MPa, and (d) is the impact compression failure morphology diagram when the air pressure value is 0.7 MPa.
[0030] Figure 7 The impact compression failure morphology diagrams of the ultra-high performance concrete of comparative example 1 at different strain rates; (a) is the impact compression failure morphology diagram when the air pressure value is 0.4 MPa, (b) is the impact compression failure morphology diagram when the air pressure value is 0.5 MPa, (c) is the impact compression failure morphology diagram when the air pressure value is 0.6 MPa, and (d) is the impact compression failure morphology diagram when the air pressure value is 0.7 MPa.
[0031] Figure 8 The impact compression failure morphology diagrams of the ultra-high performance concrete of comparative example 2 at different strain rates; (a) is the impact compression failure morphology diagram when the air pressure value is 0.4 MPa, (b) is the impact compression failure morphology diagram when the air pressure value is 0.5 MPa, (c) is the impact compression failure morphology diagram when the air pressure value is 0.6 MPa, and (d) is the impact compression failure morphology diagram when the air pressure value is 0.7 MPa.
[0032] Fig. 9 The impact compression failure morphology diagrams of the ultra-high performance concrete of comparative example 3 at different strain rates; (a) is the impact compression failure morphology diagram when the air pressure value is 0.4 MPa, (b) is the impact compression failure morphology diagram when the air pressure value is 0.5 MPa, (c) is the impact compression failure morphology diagram when the air pressure value is 0.6 MPa, and (d) is the impact compression failure morphology diagram when the air pressure value is 0.7 MPa.
[0033] Fig.10 The figures are the dynamic splitting failure morphology diagrams of the ultra-high performance concrete of Example 1 at different strain rates; (a) is the dynamic splitting failure morphology diagram when the air pressure value is 0.3 MPa, (b) is the dynamic splitting failure morphology diagram when the air pressure value is 0.4 MPa, (c) is the dynamic splitting failure morphology diagram when the air pressure value is 0.5 MPa, and (d) is the dynamic splitting failure morphology diagram when the air pressure value is 0.6 MPa.
[0034] Fig.11The figures are the dynamic splitting failure morphology diagrams of the ultra-high performance concrete of comparative example 1 at different strain rates; (a) is the dynamic splitting failure morphology diagram when the air pressure value is 0.3 MPa, (b) is the dynamic splitting failure morphology diagram when the air pressure value is 0.4 MPa, (c) is the dynamic splitting failure morphology diagram when the air pressure value is 0.5 MPa, and (d) is the dynamic splitting failure morphology diagram when the air pressure value is 0.6 MPa.
[0035] Fig.12 The figures are the dynamic splitting failure morphology diagrams of the ultra-high performance concrete of comparative example 2 at different strain rates; (a) is the dynamic splitting failure morphology diagram when the air pressure value is 0.3 MPa, (b) is the dynamic splitting failure morphology diagram when the air pressure value is 0.4 MPa, (c) is the dynamic splitting failure morphology diagram when the air pressure value is 0.5 MPa, and (d) is the dynamic splitting failure morphology diagram when the air pressure value is 0.6 MPa.
[0036] Fig.13 The figures are the dynamic splitting failure morphology diagrams of the ultra-high performance concrete of comparative example 3 at different strain rates; (a) is the dynamic splitting failure morphology diagram when the air pressure value is 0.3 MPa, (b) is the dynamic splitting failure morphology diagram when the air pressure value is 0.4 MPa, (c) is the dynamic splitting failure morphology diagram when the air pressure value is 0.5 MPa, and (d) is the dynamic splitting failure morphology diagram when the air pressure value is 0.6 MPa. DETAILED DESCRIPTION
[0037] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0038] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0039] A typical embodiment of the present invention provides an impact-resistant ultra-high performance concrete, which is prepared from the following raw materials in parts by weight:
[0040] 15-30 parts of micron-grade magnesium oxide, 15-30 parts of nano-grade magnesium oxide, 800-900 parts of cement, 100-130 parts of silica fume, 90-120 parts of fly ash microspheres, 280-320 parts of medium sand, 650-750 parts of fine sand, 130-170 parts of modified steel fiber, 15-30 parts of water reducer and 140-160 parts of water;
[0041] The modified steel fiber is a steel fiber modified by a hydrolyzate of a silane coupling agent; the length of the steel fiber is 1.3-50 mm, and the diameter is 0.10-0.20 mm;
[0042] Among the steel fibers, the volume percentage of steel fibers with a length of 1.3-20 mm is 25-35%, the volume percentage of steel fibers with a length of 20-40 mm is 35-45%, and the volume percentage of steel fibers with a length of 40-50 mm is 25-35%.
[0043] Through the above components, steel fibers with a large length range are used to inhibit the expansion of large cracks and micro cracks, and the bonding performance between the steel fibers and the UHPC matrix is improved through silane modification; the self-shrinkage of UHPC is reduced by multi-scale magnesium oxide compensation shrinkage to further improve the bonding performance between the steel fibers and the UHPC matrix, so that UHPC with excellent impact resistance can be obtained.
[0044] Optionally, the particle size of micron-sized magnesium oxide is 5~10µm, the average particle size is 4µm, and the specific surface area is 0.16~0.34m 2 / g.
[0045] Optionally, the particle size of nano-magnesium oxide is 100~500nm, the average particle size is 400nm, and the specific surface area is 3.36~16.8m 2 / kg.
[0046] Optionally, the cement is ordinary Portland cement of PO 52.5 or PO 52.5R, which has good compatibility with the polycarboxylate water reducer.
[0047] Optionally, the mass percentage of silicon dioxide in the silica ash is not less than 97%, the volcanic ash activity index is greater than 95%, and the specific surface area is greater than 21.0 m 2 / g.
[0048] Optionally, the fly ash microbeads are derived from Class F fly ash, and the fineness is Class I ash.
[0049] Optionally, the medium sand is quartz sand or silica sand with a particle size of 24 to 40 meshes.
[0050] Optionally, the fine sand is quartz sand or silica sand with a particle size of 40-80 mesh.
[0051] Optionally, the water reducing agent is a standard high-performance water reducing agent with a water reduction rate greater than 25%.
[0052] Optionally, the steel fiber is a straight steel fiber or a waste tire steel fiber.
[0053] Common raw materials for UHPC include copper-plated straight steel fibers. In terms of cost, the cost of copper-plated straight steel fibers with a volume content of only 1% exceeds the cost of other UHPC materials. In order to reduce the cost of copper-plated straight steel fibers, waste tire steel fibers are used as alternative materials. Waste tire steel fibers are obtained by simple processes such as stripping and cutting the steel wire belt layer in waste tires through physical means; the curved shape, end hooks and rough surface formed by mechanical processing during the recycling process of waste tire steel fibers can be used to make them more firmly bonded to the substrate.
[0054] The preparation method of the above-mentioned impact-resistant ultra-high performance concrete comprises:
[0055] S1. Soak the steel fiber in a sodium hydroxide solution with a mass concentration of 20-35% for 20-40 min, then take it out and wash it;
[0056] S2, soaking the washed steel fiber in a silane coupling agent hydrolyzate for 7-15 minutes, then taking it out, and drying it at 100-120° C. for 1.5-2.5 hours to obtain a modified steel fiber;
[0057] S3, mixing micron-sized magnesium oxide, nano-sized magnesium oxide, cement, silica fume, fly ash microbeads, medium sand and fine sand, and dry-mixing for 3-5 minutes to obtain a first mixed material;
[0058] S4, adding water and a water reducing agent to the first mixed material, stirring for 5 to 7 minutes, to obtain a second mixed material;
[0059] S5, adding modified steel fiber to the second mixed material in a stirring state for several times, stirring for 6 to 8 minutes, to obtain a concrete mixture;
[0060] S6. Cast the concrete mixture into a mold, cover it with a curing film, demould it after a set time and cure it to the specified age.
[0061] Optionally, in S1, after taking out, the sample is washed with deionized water and anhydrous ethanol in sequence to remove residual sodium hydroxide solution.
[0062] Optionally, in S2, the raw materials for preparing the silane coupling agent hydrolyzate include a silane coupling agent, deionized water and anhydrous ethanol in a volume ratio of 1:(3-5):(7-10).
[0063] Optionally, the silane coupling agent is silane coupling agent KH-550.
[0064] Optionally, the method for preparing the silane coupling agent hydrolyzate includes: mixing the silane coupling agent solution, anhydrous ethanol and deionized water in a set ratio, stirring for a set time, and completing the preparation of the hydrolyzate.
[0065] Optionally, in S6, the specimen is demoulded after being cured in a molding room for 24 h, and then cured in a standard curing room to a specified age.
[0066] Example 1
[0067] This embodiment provides an impact-resistant ultra-high performance concrete, comprising the following components in parts by weight:
[0068] 22.32 parts of micron-grade magnesium oxide, 22.32 parts of nano-grade magnesium oxide, 850.56 parts of cement, 115.2 parts of silica fume, 105.6 parts of fly ash microspheres, 306 parts of medium sand, 706 parts of fine sand, 156 parts of modified waste tire steel fiber, 20 parts of water reducer and 150 parts of water;
[0069] The modified waste tire steel fiber is: waste tire steel fiber modified by silane coupling agent hydrolyzate;
[0070] Waste tire steel fiber comes from different types of discarded rubber tires. The internal steel cord varies depending on the tire model. The specific specifications are: the length of the steel fiber is 1.3~50mm, the average diameter is 0.18mm, and the tensile strength is 2165MPa; among them, the volume percentage of steel fibers with a length of 1.3~20mm is 30%, the volume percentage of steel fibers with a length of 20~40mm is 40%, and the volume percentage of steel fibers with a length of 40~50mm is 30%.
[0071] The particle size of micron-sized magnesium oxide is 4µm, and the particle size of nano-sized magnesium oxide is 400nm.
[0072] The cement is PO 52.5 ordinary Portland cement.
[0073] The mass percentage of silicon dioxide in silica ash is not less than 97%, the volcanic ash activity index is greater than 95%, and the specific surface area is greater than 21.0m 2 / g, density is 2.20g / cm 3 .
[0074] Fly ash microbeads are derived from Class F fly ash, with a fineness of Class I and a specific gravity of 2.52.
[0075] Medium sand is quartz sand with a mesh size of 24~40.
[0076] The fine sand is quartz sand of 40~80 mesh.
[0077] The water reducing agent is a standard high-performance water reducing agent with a water reduction rate greater than 25%.
[0078] The preparation method comprises:
[0079] S1. The steel wire belt layer in the waste tire is stripped and cut by physical means to obtain waste tire steel fiber, and the waste tire steel fiber is soaked in a sodium hydroxide solution with a mass concentration of 20% for 30 minutes. Then it is taken out and washed with deionized water and anhydrous ethanol to remove the residual sodium hydroxide solution.
[0080] S2. Mix KH-550, anhydrous ethanol and deionized water in a volume ratio of 1:3:9, stir for 30 minutes and then let stand for 3 hours to complete the preparation of the silane coupling agent hydrolyzate; soak the washed waste tire steel fiber in S1 in the silane coupling agent hydrolyzate, take it out after 10 minutes, and dry it at 110°C for 2 hours to obtain modified waste tire steel fiber.
[0081] S3. Mix micron-sized magnesium oxide, nano-sized magnesium oxide, cement, silica fume, fly ash microbeads, medium sand and fine sand in a prescribed ratio and dry-mix for 3 minutes to obtain a first mixed material.
[0082] S4. Add water and a water reducing agent to the first mixed material, and stir for 5 minutes to obtain a second mixed material.
[0083] S5, adding modified waste tire steel fiber to the second mixed material in a stirring state by sprinkling it in multiple times, and continuing to stir for 6 minutes after the sprinkling is completed to obtain a concrete mixture; Figure 1 As shown in (b), due to the slightly curved geometry and different lengths of the scrap tire steel fibers, some scrap tire steel fibers tend to clump together. In order to ensure that the scrap tire steel fibers can be evenly dispersed in the concrete mixture, the clumped scrap tire steel fibers should be separated before preparing the concrete mixture, and then added evenly and slowly into the mixer for mixing.
[0084] S6. After testing the fluidity of the concrete mixture, cast the mold, smooth it with a trowel, and cover it with plastic film. The specimens with the mold are cured in the molding room for 24 hours, and then demolded and numbered with a demoulding gun. The demolded and numbered specimens are cured in a standard curing room to the specified age.
[0085] Example 2
[0086] This embodiment provides an impact-resistant ultra-high performance concrete, comprising the following components in parts by weight:
[0087] 22.32 parts of micron-grade magnesium oxide, 22.32 parts of nano-grade magnesium oxide, 850.56 parts of cement, 115.2 parts of silica fume, 105.6 parts of fly ash microspheres, 306 parts of medium sand, 706 parts of fine sand, 156 parts of modified steel fiber, 20 parts of water reducer and 150 parts of water;
[0088] The modified steel fiber is a straight steel fiber modified by a hydrolyzate of a silane coupling agent.
[0089] The length of straight steel fiber is 1.3~50mm, the average diameter is 0.18mm, and the tensile strength is 2165MPa; among them, the volume percentage of steel fiber with a length of 1.3~20mm is 30%, the volume percentage of steel fiber with a length of 20~40mm is 40%, and the volume percentage of steel fiber with a length of 40~50mm is 30%.
[0090] The particle size of micron-sized magnesium oxide is 4µm, and the particle size of nano-sized magnesium oxide is 400nm.
[0091] The cement is PO 52.5 ordinary Portland cement.
[0092] The mass percentage of silicon dioxide in silica ash is not less than 97%, the volcanic ash activity index is greater than 95%, and the specific surface area is greater than 21.0m 2 / g, density is 2.20g / cm 3 .
[0093] Fly ash microbeads are derived from Class F fly ash, with a fineness of Class I and a specific gravity of 2.52.
[0094] Medium sand is quartz sand with a mesh size of 24~40.
[0095] The fine sand is quartz sand of 40~80 mesh.
[0096] The water reducing agent is a standard high-performance water reducing agent with a water reduction rate greater than 25%.
[0097] The preparation method comprises:
[0098] S1. Soak the straight steel fiber in a 20% sodium hydroxide solution for 30 min. Then take it out and wash it with deionized water and anhydrous ethanol to remove the residual sodium hydroxide solution.
[0099] S2. Mix KH-550 solution, anhydrous ethanol and deionized water in a volume ratio of 1:3:9, stir for 30 minutes and then let stand for 3 hours to complete the preparation of the silane coupling agent hydrolyzate; soak the straight steel fiber washed in S1 in the silane coupling agent hydrolyzate, take it out after 10 minutes, and dry it at 110°C for 2 hours to obtain the modified straight steel fiber.
[0100] S3. Mix micron-sized magnesium oxide, nano-sized magnesium oxide, cement, silica fume, fly ash microbeads, medium sand and fine sand in a prescribed ratio and dry-mix for 3 minutes to obtain a first mixed material.
[0101] S4. Add specified mass fractions of water and water reducing agent to the first mixed material, stir for 5 minutes, and obtain a second mixed material.
[0102] S5. Add the modified straight steel fiber to the second mixed material in a stirring state by sprinkling it in multiple times. After sprinkling, continue stirring for 6 minutes to obtain a concrete mixture.
[0103] S6. After testing the fluidity of the concrete mixture, cast the mold, smooth it with a trowel, and cover it with plastic film. The specimens with the mold are cured in the molding room for 24 hours, and then demolded and numbered with a demoulding gun. The demolded and numbered specimens are cured in a standard curing room to the specified age.
[0104] Comparative Example 1
[0105] This comparative example provides an impact-resistant ultra-high performance concrete, comprising the following components in parts by weight:
[0106] 850.56 parts of cement, 115.2 parts of silica fume, 105.6 parts of fly ash microspheres, 306 parts of medium sand, 706 parts of fine sand, 156 parts of modified waste tire steel fiber, 22 parts of water reducer and 150 parts of water.
[0107] The difference from Example 1 is that no micron-sized magnesium oxide and nano-sized magnesium oxide are added, and other raw material requirements and preparation methods are the same as those in Example 1.
[0108] Comparative Example 2
[0109] This comparative example provides an impact-resistant ultra-high performance concrete, comprising the following components in parts by weight:
[0110] 22.32 parts of micron-grade magnesium oxide, 22.32 parts of nano-grade magnesium oxide, 850.56 parts of cement, 115.2 parts of silica fume, 105.6 parts of fly ash microbeads, 306 parts of medium sand, 706 parts of fine sand, 156 parts of waste tire steel fiber, 22 parts of water reducer and 155 parts of water.
[0111] The difference from Example 1 is:
[0112] Instead of using modified waste tire steel fiber, ordinary waste tire steel fiber is used, and other raw material requirements are the same as those in Example 1;
[0113] In the preparation method, the preparation is performed according to steps S3 to S6.
[0114] Comparative Example 3
[0115] This comparative example provides an ultra-high performance concrete, comprising the following components in parts by weight:
[0116] 850.56 parts of cement, 115.2 parts of silica fume, 105.6 parts of fly ash beads, 306 parts of medium sand and 706 parts of fine sand.
[0117] The difference from Example 1 is that no micron-sized magnesium oxide and nano-sized magnesium oxide are added, no modified waste tire steel fiber is added, and other raw material requirements and preparation methods are the same as those in Example 1.
[0118] Performance Testing
[0119] The samples prepared in Example 1, Example 2, Comparative Example 1, Comparative Example 2 and Comparative Example 3 after curing were tested, and the test contents included:
[0120] According to the "Standard for Test Methods for Mechanical Properties of Ordinary Concrete" GB / T50081-2019, the cube compressive strength, splitting tensile strength and flexural strength are tested.
[0121] According to the experimental principle of Hopkinson pressure bar (SHPB), the dynamic compressive strength and dynamic splitting tensile strength were tested. This test used a SHPB device with a rod diameter of 100 mm as the impact loading equipment. The device mainly consists of a high-pressure gas tank, a striking rod (2m), an incident rod (6m), a transmission rod (4m) and an absorption rod. The rod material of the SHPB is high-strength alloy steel with a density of 7850kg / m 3 , Young's modulus is 210 GPa, the longitudinal wave velocity of the compression rod is 5172.19 m / s, and the area of the compression rod is 0.00785 m 2 . Two resistive strain gauges are attached to the surface of the incident rod and the transmission rod respectively, and the test specimen is clamped between the incident rod and the transmission rod. During the loading process, the target air pressure of the high-pressure gas tank is first input through the computer, and then the gas tank channel is opened. The high-pressure gas pushes the impact rod in the gas pipe to accelerate, and finally hits the incident rod, causing it to compress and deform and form an incident strain wave. During the process, the incident wave propagates along the incident rod, first passes through the strain gauge of the incident rod, and is recorded as incident wave data by a high-speed data acquisition instrument. Then the incident wave reaches the surface of the specimen, causing the test specimen to compress and deform. At the same time, the specimen will experience reflection and transmission phenomena, and transmit the strain wave to the incident rod and the transmission rod respectively. Then it is recorded as a reflected wave and a transmitted wave respectively through the strain gauges on the two rods. It can be seen that when the air pressure is higher, the speed of the impact rod is faster, the strain rate of the incident wave is greater, and the impact load applied to the specimen is greater.
[0122] Among them, in the dynamic compressive strength test, the air pressure values are 0.4, 0.5, 0.6 and 0.7 MPa respectively.
[0123] In the dynamic splitting tensile strength test, the gas pressure values are 0.3, 0.4, 0.5 and 0.6 MPa respectively.
[0124] Figure 2 The dynamic stress-strain curve of the ultra-high performance concrete of Example 1 under different air pressure values is as follows: when the air pressure value is 0.4 MPa, the strain rate is 50.7 / s; when the air pressure value is 0.5 MPa, the strain rate is 86.9 / s; when the air pressure value is 0.6 MPa, the strain rate is 121.6 / s; when the air pressure value is 0.7 MPa, the strain rate is 139.7 / s;
[0125] The calculation method of strain rate is:
[0126] ;
[0127] In the formula, is the strain rate, is the reflected wave strain, is the propagation speed of stress waves in the rod, is the thickness of the specimen.
[0128] Since Example 2 and Example 1 show similar performance, and the performance of Example 1 is better than that of Example 2, the following mainly analyzes Example 1 as a representative of the technical solution of the present invention, and the performance test results of Example 2 are presented in the summary table.
[0129] Figure 3 This is the dynamic stress-strain curve of the ultra-high performance concrete of comparative example 1 under different air pressure values. When the air pressure value is 0.4 MPa, the strain rate is 51.4 / s, when the air pressure value is 0.5 MPa, the strain rate is 85.2 / s, when the air pressure value is 0.6 MPa, the strain rate is 122.1 / s, and when the air pressure value is 0.7 MPa, the strain rate is 140.2 / s.
[0130] Figure 4 This is the dynamic stress-strain curve of the ultra-high performance concrete of comparative example 2 under different air pressure values. When the air pressure value is 0.4 MPa, the strain rate is 53.2 / s, when the air pressure value is 0.5 MPa, the strain rate is 86.1 / s, when the air pressure value is 0.6 MPa, the strain rate is 125.3 / s, and when the air pressure value is 0.7 MPa, the strain rate is 142.5 / s.
[0131] Figure 5 This is the dynamic stress-strain curve of the ultra-high performance concrete of comparative example 3 under different air pressure values. When the air pressure value is 0.4 MPa, the strain rate is 50.0 / s, when the air pressure value is 0.5 MPa, the strain rate is 87.5 / s, when the air pressure value is 0.6 MPa, the strain rate is 122.6 / s, and when the air pressure value is 0.7 MPa, the strain rate is 140.2 / s.
[0132] Figure 2 , Figure 3 , Figure 4 and Figure 5 The highest point in the curve is the dynamic compressive strength of UHPC at this load, and the conclusion is consistent with that in Table 1 below.
[0133] Figure 6 The impact compression failure morphology diagrams of the ultra-high performance concrete of Example 1 under different air pressure values (the higher the air pressure value, the higher the strain rate. That is, the high and low air pressure values can represent the high and low change trends of the strain rate), among which, the air pressure value of (a) is 0.4 MPa, and the corresponding strain rate is 50.7 / s, the air pressure value of (b) is 0.5 MPa, and the corresponding strain rate is 86.9 / s, the air pressure value of (c) is 0.6 MPa, and the corresponding strain rate is 121.6 / s, and the air pressure value of (d) is 0.7 MPa, and the corresponding strain rate is 139.7 / s.
[0134] Figure 7 The impact compression failure morphology of the ultra-high performance concrete of Example 1 at different strain rates, (a) has an air pressure value of 0.4 MPa, and the corresponding strain rate is 51.4 / s, (b) has an air pressure value of 0.5 MPa, and the corresponding strain rate is 85.2 / s, (c) has an air pressure value of 0.6 MPa, and the corresponding strain rate is 122.1 / s, and (d) has an air pressure value of 0.7 MPa, and the corresponding strain rate is 140.2 / s.
[0135] Figure 8 The impact compression failure morphology of ultra-high performance concrete in Example 2 at different strain rates: the air pressure value of (a) is 0.4 MPa, and the corresponding strain rate is 53.2 / s; the air pressure value of (b) is 0.5 MPa, and the corresponding strain rate is 86.1 / s; the air pressure value of (c) is 0.6 MPa, and the corresponding strain rate is 125.3 / s; the air pressure value of (d) is 0.7 MPa, and the corresponding strain rate is 142.5 / s.
[0136] Fig. 9 The impact compression failure morphology of ultra-high performance concrete in Example 3 at different strain rates: (a) has an air pressure value of 0.4 MPa, and a corresponding strain rate of 50.0 / s; (b) has an air pressure value of 0.5 MPa, and a corresponding strain rate of 87.5 / s; (c) has an air pressure value of 0.6 MPa, and a corresponding strain rate of 122.6 / s; (d) has an air pressure value of 0.7 MPa, and a corresponding strain rate of 140.2 / s.
[0137] Figure 6 , Figure 7 , Figure 8 and Fig. 9The impact compression failure morphologies of ultra-high performance concrete of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 are shown respectively, wherein each sub-figure (a), (b), (c) and (d) represent the impact compression failure morphologies under air pressure values of 0.4MPa, 0.5MPa, 0.6MPa and 0.7MPa, respectively. The higher the air pressure value, the higher the strain rate. Therefore, the high and low variation trend of the air pressure value can represent the high and low variation trend of the strain rate. It can be seen from the figure that the impact compression failure morphology of UHPC in Example 1 is not as severe as that of the other three groups, indicating that after the addition of modified steel fiber and multi-scale magnesium oxide, the failure morphology of UHPC under dynamic compression has been significantly improved.
[0138] Fig.10 , Fig.11 , Fig.12 and Fig.13 The dynamic splitting failure morphologies of the ultra-high performance concrete of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 at different strain rates are shown. Similarly, the higher the air pressure value, the higher the strain rate. Therefore, the high and low change trend of the air pressure value can represent the high and low change trend of the strain rate. Fig.10 , Fig.11 , Fig.12 and Fig.13 In each sub-figure, the air pressure value of (a) is 0.3MPa, the air pressure value of (b) is 0.4MPa, the air pressure value of (c) is 0.5MPa, and the air pressure value of (d) is 0.6MPa. It can be seen from the figure that the dynamic splitting failure morphology of UHPC in Example 1 is not as serious as that of the other three groups, indicating that after the addition of modified waste tire steel fiber and multi-scale magnesium oxide, the failure morphology of UHPC under dynamic splitting has been significantly improved.
[0139] The test results are shown in Table 1.
[0140] Table 1 Performance test results
[0141]
[0142] It can be seen from Table 1 that the mechanical properties of UHPC have been significantly improved after the addition of modified steel fiber and multi-scale magnesium oxide.
[0143] First, the static mechanical properties of UHPC shown in Example 1 and Example 2 are significantly higher than those of other groups.
[0144] Secondly, the dynamic mechanical properties of UHPC shown in Examples 1 and 2 are also significantly higher than those of other comparative examples, including dynamic compressive strength and dynamic splitting tensile strength at various strain rates. Figure 1As shown in (b), ① the length span of the steel fiber is large, and the longer steel fiber can better inhibit the crack propagation; ② the waste tire steel fiber of Example 1 is mostly curved, and there are end hooks at its ends, which can strengthen the anchoring effect between the steel fiber and the matrix; ③ the recycling process of the waste tire steel fiber of Example 1 makes its surface rougher, making the steel fiber and the matrix bond more firmly. ④ The incorporation of multi-scale magnesium oxide further enhances the bonding performance between the UHPC matrix and the steel fiber; accordingly, as Figure 1 As shown in (a), Figure 1 The magnification of (a) is Figure 1 The copper-plated straight steel fiber in the figure has the following specifications: length 13 mm, diameter 0.2 mm, and tensile strength 2850 MPa. The commercially available copper-plated straight steel fiber does not have a curved morphology and has a smooth surface, which weakens its bonding effect with the substrate.
[0145] The bonding performance between the magnesium oxide and the modified layer on the surface of the modified steel fiber is improved by silane modification, and the self-shrinkage of the UHPC is reduced by compensating the shrinkage of the multi-scale magnesium oxide, and the bonding performance between the steel fiber and the UHPC matrix is further improved. The bonding performance between the steel fiber and the matrix is improved by the above two methods, and an impact-resistant UHPC is developed. Therefore, in some indicators, the improvement of Example 1 relative to Comparative Example 3 is significantly higher than the sum of the improvement of Comparative Example 1 and Comparative Example 2 relative to Comparative Example 3. For example, in the dynamic compressive strength at 0.4MPa, the difference between Example 1 and Comparative Example 3 is 20.4MPa, the difference between Comparative Example 1 and Comparative Example 3 is 8.3MPa, and the difference between Comparative Example 2 and Comparative Example 3 is 6.5MPa. The improvement of Example 1 (20.4MPa) is greater than the sum of the improvement of Comparative Example 1 and Comparative Example 2 (8.3+6.5=14.8MPa). Correspondingly, in the dynamic compressive strength at 0.6 and 0.7 MPa, the improvement of Example 1 is significantly greater than the sum of the improvements of Comparative Example 1 and Comparative Example 2. Correspondingly, Example 2 also shows a similar performance enhancement, indicating that the technical effects of Example 1 and Example 2 exceed the superposition of the technical solutions of Comparative Example 1 and Comparative Example 2.
[0146] Therefore, the technical solutions of Example 1 and Example 2 can be applied to the construction of buildings, including anti-collision structures in bridges (which can be used to prevent collision / impact on bridges, such as ship collisions or car collisions) or anti-collision structures in high-rise buildings (which can be used to prevent collision / impact on buildings, such as large aircraft collisions, etc.).
[0147] Finally, compared with other steel fiber reinforced materials such as straight copper-plated steel fibers, the cost of waste tire steel fibers is relatively low. At the same time, it can achieve the recycling of waste resources and has high economic and environmental benefits.
[0148] In summary, the present invention has developed a low-energy, environmentally friendly green UHPC material based on modified steel fiber and multi-scale magnesium oxide, which can not only effectively reduce the cost of UHPC and reduce environmental pollution, but also has good impact resistance, providing new ideas and methods for the research and development and application of concrete materials, and showing significant technical innovation and application prospects.
[0149] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. An impact-resistant ultra-high performance concrete, characterized in that: It is prepared from the following raw materials in parts by weight: 15-30 parts of micron-grade magnesium oxide, 15-30 parts of nano-grade magnesium oxide, 800-900 parts of cement, 100-130 parts of silica fume, 90-120 parts of fly ash microspheres, 280-320 parts of medium sand, 650-750 parts of fine sand, 130-170 parts of modified steel fiber, 15-30 parts of water reducer and 140-160 parts of water; The modified steel fiber is a steel fiber modified by a hydrolyzate of a silane coupling agent; the length of the steel fiber is 1.3-50 mm, and the diameter is 0.10-0.20 mm; Among the steel fibers, the volume percentage of steel fibers with a length of 1.3 to 20 mm is 25 to 35%, the volume percentage of steel fibers with a length of 20 to 40 mm is 35 to 45%, and the volume percentage of steel fibers with a length of 40 to 50 mm is 25 to 35%; The steel fiber is waste tire steel fiber or straight steel fiber.
2. The impact-resistant ultra-high performance concrete according to claim 1, characterized in that: The particle size of micron-sized magnesium oxide is 5~10µm, the average particle size is 4µm, and the specific surface area is 0.16~0.34m 2 / g; the particle size of nano-magnesium oxide is 100~500nm, the average particle size is 400nm, and the specific surface area is 3.36~16.8m 2 / kg.
3. The impact-resistant ultra-high performance concrete according to claim 1, characterized in that: The cement is ordinary Portland cement of PO 52.5 or P.O52.5R.
4. The impact-resistant ultra-high performance concrete according to claim 1, characterized in that: The mass percentage of silicon dioxide in the silica ash is not less than 97%, the volcanic ash activity index is greater than 95%, and the specific surface area is greater than 21.0m 2 / g.
5. The impact-resistant ultra-high performance concrete according to claim 1, characterized in that: The fly ash microbeads are derived from Class F fly ash, and the fineness is Class I ash.
6. The impact-resistant ultra-high performance concrete according to claim 1, characterized in that: The medium sand is quartz sand or silica sand with a particle size of 24-40 meshes; the fine sand is quartz sand or silica sand with a particle size of 40-80 meshes; the water reducer is a standard high-performance water reducer with a water reduction rate greater than 25%.
7. A method for preparing the impact-resistant ultra-high performance concrete according to any one of claims 1 to 6, characterized in that the steps include: S1. Soak the steel fiber in a sodium hydroxide solution with a mass concentration of 20-35% for 20-40 min; S2, soaking the washed steel fiber in a silane coupling agent hydrolyzate for 7-15 minutes, then taking it out, and drying it at 100-120° C. for 1.5-2.5 hours to obtain a modified steel fiber; S3, mixing micron-sized magnesium oxide, nano-sized magnesium oxide, cement, silica fume, fly ash microbeads, medium sand and fine sand, and dry-mixing for 3-5 minutes to obtain a first mixed material; S4, adding water and a water reducing agent to the first mixed material, stirring for 5 to 7 minutes, to obtain a second mixed material; S5, adding modified steel fiber to the second mixed material in a stirring state for several times, stirring for 6 to 8 minutes, to obtain a concrete mixture; S6. Cast the concrete mixture into a mold, cover it with a curing film, demould it after a set time and cure it to the specified age.
8. The method for preparing impact-resistant ultra-high performance concrete with added waste tire steel fiber as claimed in claim 7, characterized in that: In S2, in the raw materials for preparing the silane coupling agent hydrolyzate, the volume ratio of the silane coupling agent, deionized water and anhydrous ethanol is 1: (3-5): (7-10); the silane coupling agent is silane coupling agent KH-550.
9. Use of the impact-resistant ultra-high performance concrete according to any one of claims 1 to 6 in building construction.
Citation Information
Patent Citations
180 MPa ultra-high-performance concrete and preparation method thereof
CN107265983A
Anti-crack ultra-high performance concrete pole and preparation method thereof
CN114477885A
Hybrid fiber reinforced ultra-high performance concrete
CN114920504A
High-ductility multi-scale fiber reinforced cement-based composite material and preparation method thereof
CN116874265A
Anti-crack ultra-high performance concrete for water-rich stratum underground engineering as well as preparation method and application of anti-crack ultra-high performance concrete
CN118184273A